Guyana: A Half a Century of Struggles with Planning, Growth, and Development. - RAMRATTAN, Lall B. (Journal of Economics and Political Economy, 2015)
Guyana was a proving ground for both the capitalist and socialist development ideas in the latter half of the 20th century. We analyze the problems and solutions for those experiment from the point of views of appraising their performances. Traditional theories such as input-output models, sectorial models, and growth models form the windows for the appraisal. When the subject matter is judgmental, Analytic Network Process and (ANP) and Data Envelop Analysis (DEA) are engaged. When the subject matter is structural, the time series of gross investment to GDP is considered as a driver of growth. We subject that ratio to spectral and cross-spectral analysis for a half a century of data for Guyana vs. neighboring countries. The results indicate that Guyana has stepped into the long-run cumulative growth process after its struggles with development. Keywords: Development, Planning, Sectorial Models, Analytic Network Process, Data Envelop Analysis, Spectral Analysis. JEL Class.:C00 (Quantitative Analysis); C15 (Simulation); C88 (Data Analysis)